Improving Weight Measurement Compliance in the Intensive Care Unit. - Ghaleb, Saba A.; Roth, Roxanne L.; Chan, Tracy; Lauderbach, Claude (Bud) (Nephrology Nursing Journal)
Fluid management is crucial in patients with end stage kidney disease, and weight measurement is an integral component of safe and effective care. Weight trends can indicate changes in volume status, especially in the acute care settings, but they are often missed. The purpose of this quality improvement project was to increase bodyweight measurement compliance rates in patients admitted to the intensive care unit by creating an automatic order generating a task list reminder on the nursing staff worklist. One month of data was collected pre-intervention and one month post intervention. Results indicate an increase in the percentage of weights taken post-intervention (M = 62.1%, SD = 11.2; p = 0.001) compared to pre-intervention (M = 28.9%, SD = 9.8).